Dampak Alih Fungsi Lahan Pertanian Bagi Kesejahteraan Buruh Tani di Desa Panji Anom - Dewantara, Putu Tegar; Suwena, Kadek Rai (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the impact of agricultural land-use conversion on the welfare of farm laborers in Panji Anom Village. This research is classified as a descriptive study with a qualitative approach. In the data collection process, the researcher focused on gathering descriptive data, with the research subjects being farmers and farm laborers in Panji Anom Village, who provided the necessary information based on field conditions. The object of this research is the impact of agricultural land-use conversion on the welfare of farm laborers. The data collection methods used include observation, interviews, and documentation. This study employs a qualitative analysis technique developed by Miles and Huberman, which includes data collection, data reduction, data presentation, and conclusion drawing. The study finds that the conversion of agricultural land in Panji Anom Village is driven by economic pressures, crop failures, and the declining interest of the younger generation in farming. Much of the agricultural land has been converted into residential areas, resulting in decreased job opportunities and income for farm laborers, as well as increased economic vulnerability in the village community.